2008
DOI: 10.1126/science.1154619
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Environmental Health Protection

Abstract: POLICYFORUMWe propose a shift from primarily in vivo animal studies to in vitro assays, in vivo assays with lower organisms, and computational modeling for toxicity assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
431
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 584 publications
(437 citation statements)
references
References 7 publications
3
431
0
3
Order By: Relevance
“…At this point, the computational results are expected to interpret the experimental findings and provide theoretical support for the conclusions of the experimental MPB degradation results. In addition, as a approach of cost-effective, convenient, and avoiding the use of animals for toxicological study [22,23], computational approach is frequently adopted to investigate the molecular basis of environmental, chemical, and biological processes [24,25]. To date, no computational study has been reported on the mechanisms and kinetics of MPB degradation using AOPs, as well as the toxicity assessment of its degradation products.…”
Section: Introductionmentioning
confidence: 99%
“…At this point, the computational results are expected to interpret the experimental findings and provide theoretical support for the conclusions of the experimental MPB degradation results. In addition, as a approach of cost-effective, convenient, and avoiding the use of animals for toxicological study [22,23], computational approach is frequently adopted to investigate the molecular basis of environmental, chemical, and biological processes [24,25]. To date, no computational study has been reported on the mechanisms and kinetics of MPB degradation using AOPs, as well as the toxicity assessment of its degradation products.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the NTP, the NIH Chemical Genomics Center, and the U.S. Environmental Protection Agency initiated the Tox21 program for the development and validation of in vitro assays through the use of a high-throughput screening (HTS) platform. [11][12][13] Various in vitro approaches have been described in the literature to screen for hepatotoxicity. [14][15][16][17][18] Recently, the advent of quantitative high-throughput screening (qHTS) has enabled researchers to obtain inhibitory concentration at 50% (IC 50 ) values directly from primary ABBREVIATIONS: ATP, adenosine triphosphate; CV, coefficient of variation; CYP, cytochrome P450; DILI, drug-induced liver injury; DMSO, dimethyl sulfoxide; FRD, flying reagent dispenser; HCS, high content screening; HTS, high-throughput screening; IC 50 , inhibitory concentration at 50%; LC/MS/MS, liquid chromatography tandem mass spectrometry; NTP, National Toxicity Program; qHTS, quantitative high-throughput screening; S/B, signal to background; SD, standard deviation; ST, sulfotransferase; UGT, UDP-glucuronosyltransferase; UPLC/MS/MS, ultra performance liquid chromatography tandem mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…2011. 50 substâncias disponíveis no mercado, resultando numa utilização química com potenciais riscos ainda desconhecidos e descontrolados (COLLINS et al, 2008;USEPA, 2003 p. 3 A Toxicologia Computacional pode ser definida como a área da Toxicologia, na qual aplica-se modelos computacionais e matemáticos para a predição de Os estudos QSAR partem da premissa básica de que existe uma relação entre as características (físico-químicas, topológicas, tridimensionais e conformacionais) de uma estrutura química e a atividade biológica, no contexto de nossa discussão, a toxicidade. A contribuição para a atividade biológica pode então ser atribuída a descritores estruturais, com uso de modelos matemáticos, estimando-se a potenciação ou redução da atividade a partir da inserção de substituintes na estrutura (OECD, 2010).…”
Section: Isbn 1984-3577unclassified